O cuidado de si e o corpo: contribuições foucaultianas para a educação escolar de adolescentes - Silva, Viviane Gonçalves (2017)
This dissertation is the result of a bibliographical research. In this work the objective is to establish a relation between Foucault's concept of self‟s care, body and education. This study proposal comes up from a concern about the way adolescents (boys/girls) have dealt with their own bodies and how this emerges in the school context. From a deepening in the foucaultian referential, other complementary readings and a reflection on practice, it is seeking to answer: What are the contributions that Foucault's concept of self‟s care can provide for school education in order to promote the body care? It is believed that the perspective of the self‟s care provides subsidies for an education that does not corroborate with the violence against teenage bodies. It is observed that the self‟s care emerges as a potent and unique perspective to rethink about education and dilemmas of human formation. Based on the proposition about self‟s care and care of others and considering freedom as a premise, educators (he/she) can guide their practice to promote a self-culture at the school space. It is hoped that this work will contribute to a debate about the body, especially at the school context and to (re)think about the formation and practice of educators (he/she), contributing to the transformation of make educational and the strengthening of the adolescents (boys/girls) on imposed subjection and violence incited against the bodies.